TOURIST PERCEPTION OF TOUR LEDERS AT CV. BILAVA TOUR RIAU PEKANBARU - Arnanda, Dian; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The tour can not be separated from the existence of a tour leader, so the tour leader is required to be able to assist tour operators in handling guests while on the trip. Which later can serve the wishes or needs of these guests. Therefore, this study was conducted to determine the perceptions of tourists towards tour leaders in Cv Bilava Tour Riau Pekanbaru. This study uses quantitative descriptive methods to examine the issues raised. The sample in this study was 100 respondents, taken using Simple Random Sampling. While the data collection techniques in this study used observation, interviews, questionnaires, and documentation. By using a Likert scale as a measuring tool to determine the length of short intervals. From the results of research conducted, it appears that the leader of the trip at Cv Bilava Tour Riau Pekanbaru is very satisfying.Â Â Keywords: tourist perception, tour leader.